Tractography-Based Analysis of Morphological and Anatomical Characteristics of the Uncinate Fasciculus in Human Brains - Kierońska, Sara (Brain Sci, 2020)
(1) Background: The uncinate fasciculus (UF) is a white matter bundle connecting the prefrontal cortex and temporal lobe. The functional role of the uncinate fasciculus is still uncertain. The role of the UF is attributed to the emotional empathy network. The present study aimed to more accurately the describe anatomical variability of the UF by focusing on the volume of fibers and testing for correlations with sex and age. (2) Material and Methods: Magnetic resonance imaging of adult patients with diffusion tensor imaging (DTI) was performed on 34 patients. The total number of fibers, volume of UF, and number of tracts were processed using DSI studio software. The DSI studio allows for mapping of different nerve pathways and visualizing of the obtained results using spatial graphics. (3) Results: The total number of UF tracts was significantly higher in the right hemisphere compared to the left hemisphere (right M ± SD = 52 ± 24; left: 39 ± 25, p < 0.05). A hook-shaped UF was the most common variant (91.7%). The UF volumes were larger in men (1410 ± 150.7 mm(3)) as compared to women (1325 ± 133.2 mm(3)) (p < 0.05). The mean fractional anisotropy (FA) values of the UF were significantly larger on the left side 0.597, while the right UF had an average of 0.346 (p < 0.05). Patients older than 50 years old had a significantly higher value of mean diffusivity (MD) (p = 0.034). In 73.5% of patients, a greater number of fibers terminated in the inferior part of the inferior frontal gyrus. (4) Conclusions: The morphological characteristics of the UF, unlike the shape, are associated with sex and are characterized by hemispheric dominance. These findings confirm the results of the previous studies. Future research should examine the potential correlation among the UF volume, number of fibers, and total brain volume in both sexes and patient psychological state.